Economic and Environmental Performance Improvements Based on S-100 Hydrographic Information - Choi, HyunSoo; Ju, HyunA; Oh, SeWoong; Park, HyunGoo (Sensors and Materials, 2025)
In this study, we empirically analyzed the impact of dynamic hydrographic information provided by the next-generation hydrographic standard S-100 on the economic efficiency of maritime transport and environmental protection. Unlike the existing S-57 standard, the S-100 standard offers dynamic hydrographic information, including real-time changes in tides, currents, and weather, which can improve the safety and efficiency of ship operations. Using the Full Mission Shipping Simulator for Mokpo–Jeju routes, we quantitatively assessed the economic effects of S-111 surface currents with the S-100 Electronic Chart Display and Information System and S-101 Electronic Navigational Charts on fuel consumption, sailing distance, and travel time, as well as the environmental benefits, such as reductions in air pollutant emissions.